Use and Protection of Water Resources - Meliyev Muzaffar Saidakbarovich; Dehqonova Jumagul Madamin qizi; Axmadjonova Zulxumorxon Nazirjon qizi (International Journal on Orange Technologies, 2021)
This article will talk about one of the current global problems - the problem of water. The article also presents the world's water resources and needs for them, the differences between them